Правові основи запровадження співпраці держави і приватних структур в Україні - Огій, О. С.; Ohii, O. S. (Право і безпека. - 2013. - № 3 (50). - С. 127-129, 2013)
Досліджено правові передумови функціонування державно-приватного партнерства і запропоновано зміни до чинного законодавства, які націлені на якісне удосконалення і поглиблення впливу держави на приватноправові відносини. Автору вбачається за необхідне уточнити в змісті базового закону з державно-приватного партнерства, що у рамках державно-приватного партнерства договори мають укладатися у письмовій формі і доповнити положенням про те, що обʼєктом державно-приватного партнерства не можуть бути обʼєкти, які не підлягають приватизації.

Legal prerequisites of state and private partnership functioning in Ukraine are researched in the paper; some alterations into current legislation aimed at qualitative improvement of stateʼs influence on private legal relations in economical sphere are offered. It is determined that the main tasks in this sphere include establishment, expansion and maintenance of a network of business centers, business incubators, innovation centers, technology parks and other infrastructureʼs facilities, entrepreneurshipʼs legal support, creation of conditions for the development of selfregulatory organizations with the gradual transfer of a part of functions on state regulation and economic activity control as well as informational guaranteeing. It seems necessary to clarify, within the content of the basic law regulating relations of state and private partnership, the norm establishing that contracts must be concluded in a written form in the framework of state and private partnership. It is also necessary to add the provision that the object of state and private partnership can not be objects that are not subjects of privatization.

Исследованы правовые предпосылки функционирования государственно-частного партнерства в Украине и предложены изменения в действующее законодательство, нацеленные на качественное усовершенствование влияния государства на частноправовые отношения в хозяйственной деятельности. Автору представляется необходимым уточнить в содержании базового закона, регулирующего отношения государственно-частного партнерства, норму, устанавливающую, что в рамках государственно-частного партнерства договоры должны заключаться в письменной форме, и дополнить положением о том, что объектом государственно-частного партнерства не могут быть объекты, которые не подлежат приватизации.
Legal grounds of cooperation between a state and a private organization in Ukraine
Правовые основы сотрудничества государства и частных структур в Украине
Огій, О. С. Правові основи запровадження співпраці держави і приватних структур в Україні / О. С. Огій // Право і безпека. - 2013. - № 3 (50). - С. 127-129.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; державно-приватне партнерство; государственно-частное партнерство; state and private partnership; правові засади; правовые основы; legal basis; законодавство; законодательство; legislation